Frequency of amino acid changes associated with resistance to attachment inhibitor BMS-626529 in R5- and X4-tropic HIV-1 subtype B - Soulie, C.; Lambert-Niclot, S.; Fofana, D. B.; Fourati, S.; Ait-Arkoub, Z.; Sayon, S.; Simon, A.; Katlama, C.; Calvez, V.; Marcelin, A.-G. (Journal of antimicrobial chemotherapy, 2013)
Resistance to attachment inhibitor BMS-626529, which inhibits the binding of HIV to CD4, involves mutations in the HIV-1 gp120 gene. There is a lack of information on the primary resistance of HIV-1 subtype B to attachment inhibitors, so we decided to investigate. Sequences from 109 attachment-inhibitor-naive patients infected with HIV-1 subtype B were analysed for the presence of previously described in vivo resistance mutations associated with attachment inhibitor BMS-626529 and tropism determination. The M426L substitution associated with a reduced efficacy of the attachment inhibitor BMS-626529 was present at 7.3%. There was no difference in mutation distribution according to virus tropism (R5 or X4). The attachment inhibitor BMS-626529 is suitable for most patients infected with HIV-1 subtype B.